Electrophysiological confirmation of the zona incerta as a target for surgical treatment of disabling involuntary arm movements in multiple sclerosis: use of local field potentials. - Nandi, D; Chir, M; Liu, X; Bain, P; Parkin, S; Joint, C; Winter, J; Stein, J; Scott, R; Gregory, R; Aziz, T (2002)
Lesioning or chronic deep brain stimulation (DBS) of the nucleus ventralis intermedius results in abolition of tremor in the contralateral limbs in Parkinson's disease (PD) and also in essential tremor. Recently, chronic DBS of the subthalamic nucleus has also proved to be very effective in reducing contralateral limb tremor in PD. These targets have been less effective in controlling the complex limb tremor often seen in multiple sclerosis (MS). Consequently, other targets have been sought in cases of MS with tremor. We describe a patient with MS with disabling proximal and distal involuntary arm movements in whom we were able to obtain sustained control of contralateral arm tremor and achieve functional improvement of the affected arm by chronic DBS of the region of the zona incerta. We also highlight the important role played by local field potentials recorded from the brain, with simultaneous recording of corresponding EMGs, in target localisation.